Dual function of angiogenin-4 inducing intestinal stem cells and apoptosis - Abo, Hirohito; Sultana, Mst. Farzana; Kawashima, Hiroto (Frontiers in Cell and Developmental Biology, 2023)
The intestinal epithelium is the first line of host defense, and its homeostasis is dependent on soluble factors that comprise the crypt niche. Antimicrobial proteins are one of the mediators to maintain gut homeostasis. Angiogenin-4 (Ang4) is a member of the ribonuclease A superfamily and plays a pivotal role in antimicrobial activity against gut microbiota. However, the functions of Ang4 within the intestinal crypt niche, particularly its involvement in the development of intestinal epithelial cells (IECs), remain unknown. Here, we demonstrate that Ang4 plays a significant role in maintaining Lgr5+ intestinal stem cells (ISCs) and induces apoptosis of IECs in a concentration-dependent manner. We revealed that Ang4 is highly expressed by Paneth cells in the small intestine, as well as regenerating islet-derived family member-4 (Reg4) expressing goblet cells in the colon, and both cell subsets highly contribute to ISC maintenance. Functional analysis using intestinal organoids revealed that Ang4 induces Wnt and Notch signaling, increases Lgr5+ stem cell expansion, and promotes organoid growth. Furthermore, high concentrations of Ang4 induced apoptosis in the IEC cell line and organoids. Collectively, we propose that Ang4 is a dual functional protein and is a novel member of the crypt niche factor that promotes the expansion of ISCs and induces apoptosis.